Perspectives in Breast and Ovarian Cancer Chemotherapy by Nanomedicine Approach: Nanoformulations in Clinical Research - Martín-Sabroso, Cristina; Fraguas-Sánchez, Ana I.; Raposo-González, Rafaela; Torres-Suárez, Ana Isabel (Current Medicinal Chemistry, 2021)
Background: Breast and ovarian carcinomas represent major health problems in women worldwide. Chemotherapy constitutes the main treatment strategy, and the use of nanocarriers, a good tool to improve it. Several nanoformulations have already been approved, and others are under clinical trials for the treatment of both types of cancers. Objective: This review focuses on the analysis of the nanoformulations that are under clinical research in the treatment of these neoplasms. Results: Currently, there are 6 nanoformulations in clinical trials for breast and ovarian carcinomas, most of them in phase II and phase III. In the case of breast cancer treatment, these nanomedicines contain paclitaxel; and, for ovarian cancer, nanoformulations containing paclitaxel or camptothecin analogs are being evaluated. The nanoencapsulation of these antineoplastics facilitates their administration and reduces their systemic toxicity. Nevertheless, the final approval and commercialization of nanoformulations may be limited by other aspects like lack of correlation between the efficacy results evaluated at in vitro and in vivo levels, difficulty in producing large batches of nanoformulations in a reproducible manner and high production costs compared to conventional formulations of antineoplastics. However, these challenges are not insurmountable and the number of approved nanoformulations for cancer therapy is growing. Conclusion: Reviewed nanoformulations have shown, in general, excellent results, demonstrating a good safety profile, a higher maximum tolerated dose and a similar or even slightly better antitumor efficacy compared to the administration of free drugs, reinforcing the use of nano-chemotherapy in both breast and ovarian tumors.
Keywords: paclitaxel